Invitro antibacterial activity of Cassia fistula Linn methanolic leaf extracts - Kamath, Bindhu R.; Kizhedath, Sabeena (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Cassia fistula Linn is a plant which is widely grown in India and is used for medicinal purposes. The study was carried out with an objective to demonstrate the antimicrobial activity of leaves of Cassia fistula Linn. The aim of the study is to assess antibacterial and antifungal activity of methanolic leaf extract of Cassia fistula Linn against selected clinical isolates. Methods: The antimicrobial activity of methanolic extract of Cassia fistula was evaluated using agar well diffusion method and to zone of inhibition of extract was determined. Clinical isolates of Staphyloccocus aureus, MRSA, Pseudomonas aeruginosa, E. coli and Proteus were screened. Results: The methanolic extracts exhibited antibacterial activity against Staphylococcus aureus. The extract was not active against E. coli, Proteus, MRSA, Pseudomonas aeruginosa. The extract also failed to demonstrate antifungal activity against Candida albicans and Aspergillus niger. Conclusions: The global emergence of multidrug resistant bacterial strains is increasing, limiting the effectiveness of current drugs and treatment failure of infections. A novel approach to the prevention of antibiotic resistance of pathogenic species is the use of new compounds that are not based on existing synthetic antimicrobial agents.